Angels and crowds - Varma, J. R. (Jayanth R.); Jacob, Joshy (London : Indian Institute of Management, Ahmedabad, 2015)
In mid 2014, two promising entrepreneurs, Kallidil Kalidasan and Nibu Alias, who needed to raise capital urgently, sought advice from Sanjay Vijaykumar, Chairman of Startup Village, on possible funding avenues and strategies. Startup Village was a technology business incubator in the state of Kerala in Southern India where both the entrepreneurs were being incubated.
Originally published in Varma, J. R., & Jacob, J. (2015). Angels and Crowds. F&A0530. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kalidasan, Kallidil; Alias, Nibu; Vijaykumar, Sanjay; New business enterprises -- Management -- India -- Case studies; Small business -- Management -- India -- Case studies; Crowd funding -- India -- Case studies; Venture capital -- India -- Case studies